1963
DOI: 10.1139/b63-010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Douglas-Fir Root Systems

Abstract: The root systems of 28 Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) in four stands, aged 10, 25, 40, and 55 years, were excavated hydraulically to determine the rooting characteristics of trees in different crown classes at various ages. The extent, depth, configuration, rooting density, and mycorrhizal component of root systems were examined. The significance of the characteristics observed is discussed in relation to silviculture, nursery practice, and forest pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

1965
1965
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…It was demonstrated long ago (Harley, 1940) that mother roots of beech grow immediately below the little layer in a horizontal plane and that they produce mycorrhizal laterals many of which grow vertically upwards away from the humified layers. More recent detailed studies of fine root production have shown that in a number of coniferous tree species the mycorrhizas are formed most extensively in the decomposition (F layers) in which the mobilization of materials is likely to be occurring at maximum rates (McMinn, 1963;Harvey, Larsen & Jurgensen, 1976;Deans, 1979;Fogel, 1983). The results presented in this and the previous paper suggest that some of the commonest ectomycorrhizal fungi would have direct access to proteins derived from plant, animal and microbial tissue in the decomposition horizon, and would therefore be capable of utilizing the resource before it became re-immobilized either in the tissues of the decomposer organisms or by being complexed with carboxylic acids in the H horizon.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated long ago (Harley, 1940) that mother roots of beech grow immediately below the little layer in a horizontal plane and that they produce mycorrhizal laterals many of which grow vertically upwards away from the humified layers. More recent detailed studies of fine root production have shown that in a number of coniferous tree species the mycorrhizas are formed most extensively in the decomposition (F layers) in which the mobilization of materials is likely to be occurring at maximum rates (McMinn, 1963;Harvey, Larsen & Jurgensen, 1976;Deans, 1979;Fogel, 1983). The results presented in this and the previous paper suggest that some of the commonest ectomycorrhizal fungi would have direct access to proteins derived from plant, animal and microbial tissue in the decomposition horizon, and would therefore be capable of utilizing the resource before it became re-immobilized either in the tissues of the decomposer organisms or by being complexed with carboxylic acids in the H horizon.…”
Section: Discussionmentioning
confidence: 99%
“…The analysed stands grew on deep soils without skeleton and none of the analysed root systems exhibited a taproot. McMinn (1963) reported the occurrence of the taproot as a juvenile form of the root system in the suppressed trees aged 30-40 years whose root systems showed only low branching. The trees analysed by us were in the main level, which may be another reason to explain why we did not found a taproot in any of them.…”
Section: Discussionmentioning
confidence: 99%
“…The slow-down of its growth has to do with the development of lateral roots, which begin to establish as taproot branches already during the first or second vegetation period (Eis 1974). Older trees feature the original taproot supplemented with branches from the main lateral roots, which penetrate the soil at a sharp angle and are rarely absolutely vertical (McMinn 1963). The root system depth in Douglas fir is determined primarily by the soil structure and texture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation reduces erosion by lessening raindrop impact, providing increased soil strength through the root network, and thus reducing surface erosion, rill erosion, and shallow bank slumps and slips (e.g., Thornes, 1985;Thorne, 1990;Prosser and Dietrich, 1995;Simon and Darby, 1999;Abernethy and Rutherford, 2001;Micheli and Kirchner, 2002). In addition, increasing tree age (and thus rooting extent and depth) is related to increasing stability of the soil (Sidle, 1987), and tree height and canopy width are proportionally related to rooting width and depth (e.g., McMinn, 1963;Smith, 1964;Tubbs, 1977;Gilman, 1989). These relationships provide a basis for using tree height as a proxy for root spread and thus soil stability as described below.…”
Section: Modifying Erosion Potential By Vegetationmentioning
confidence: 99%